Childhood Socioeconomic Disadvantage and Risk of Fatty Liver in Adulthood: The Cardiovascular Risk in Young Finns Study - Tomi T. Laitinen; Jussi Vahtera; Katja Pahkala; Costan G. Magnussen; Joel Nuotio; Nina Hutri‐Kähönen; Mika Kivimäki; Terho Lehtimäki; Eero Jokinen; Tomi Laitinen; Päivi Tossavainen; Jaana Pentti; et al. (WILEY, 2022)
Fatty liver is a preventable cause of liver failure, but early risk factors for adulthood fatty liver are poorly understood. We examined the association of childhood socioeconomic disadvantage with adulthood fatty liver and tested adulthood risk factors of fatty liver as possible mediators of this link. The study population comprised 2,042 participants aged 3-18 years at baseline (1980) from the longitudinal Cardiovascular Risk in Young Finns Study. Follow-up with repeated clinical examinations was 31 & x202f;years. Childhood socioeconomic disadvantage was assessed using data from parents' socioeconomic position and socioeconomic circumstances in participants' residential neighborhoods, categorized as high versus low socioeconomic disadvantage. Fatty liver was determined by ultrasound during the last follow-up (2011) at ages 34-49 years. Childhood and adulthood risk factors, including metabolic biomarkers and lifestyle variables, were assessed in clinical examinations. A total of 18.9% of the participants had fatty liver in adulthood. High childhood socioeconomic disadvantage was associated with an increased risk of fatty liver (risk ratio [95% confidence interval], 1.42 [1.18-1.70]; P = 0.0002). This association was robust to adjustment for age, sex, and childhood risk factors of fatty liver, including high body mass index, elevated insulin, and low birth weight (1.33 [1.09-1.62]; P = 0.005). High childhood socioeconomic disadvantage was also associated with the development of risk factors of fatty liver in adulthood. Adulthood risk factors linking childhood socioeconomic disadvantage with fatty liver included waist circumference (proportion mediated of the total effect of childhood socioeconomic disadvantage, 45%), body mass index (40%), systolic blood pressure (29%), insulin (20%), physical activity (15%), triglycerides (14%), and red meat consumption (7%). Conclusion: Childhood socioeconomic disadvantage was associated with multiple risk factors of fatty liver and increased likelihood of fatty liver in adulthood.